Heterotopic Pancreas Mimicking Metastases From Renal Carcinoma: A Rare Differential. (28th February 2023) - Datta, Deepanksha; Kumar, Rajesh; Varshney, Peeyush; Khera, Sudeep; Gupta, Tanisha
Abstract: Heterotopic pancreas, also known as ectopic or aberrant pancreas, is described as the deposits of normal pancreatic tissue "dropped" into the developing gastrointestinal system. Here we present an operated case of renal clear cell carcinoma, which on 6-month follow-up presented with eccentric mass in the gastric body suspicious for malignancy. Endoscopic biopsy was inconclusive and showed isometabolism on 18 F-FDG PET/CT. It was subsequently resected laparoscopically, and final histopathology revealed heterotopic pancreas.